2018
DOI: 10.1177/026248931803700201
|View full text |Cite
|
Sign up to set email alerts
|

Rotomolding of Foamed and Unfoamed GTR-LLDPE Blends: Mechanical, Morphological and Physical Properties

Abstract: In this work, a simple method is presented to produce ground tire rubber (GTR) -linear low density polyethylene (LLDPE) compounds and foams via rotational molding. In particular, different GTR concentrations (0 to 50% wt.) were dry-blended with different chemical blowing agent (CBA) content (0 to 1% wt.). From the samples produced, a complete set of characterization was performed in terms of mechanical properties (tensile, flexural and impact), density and morphological properties. The results show that increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 30 publications
4
11
0
Order By: Relevance
“…This picture shows that small particles are wrapping for the LLDPE matrix, although in the central part of picture appears a big particle (150 µm of length) that explains the lack of interaction between both components. These results agree with the tensile properties obtained in a manuscript published by Yao Du et al [45]. GTR particles do not reach the degradation temperature when mixing, and it is possible to see those particles dispersed in the homogeneous LLDPE polymer matrix.…”
Section: Microstructural Analysis Of the Compounds Lldpe/gtrsupporting
confidence: 92%
“…This picture shows that small particles are wrapping for the LLDPE matrix, although in the central part of picture appears a big particle (150 µm of length) that explains the lack of interaction between both components. These results agree with the tensile properties obtained in a manuscript published by Yao Du et al [45]. GTR particles do not reach the degradation temperature when mixing, and it is possible to see those particles dispersed in the homogeneous LLDPE polymer matrix.…”
Section: Microstructural Analysis Of the Compounds Lldpe/gtrsupporting
confidence: 92%
“…CBA. It has been reported that larger cells are acting as stress concentration points and easier crack propagation occurs with decreasing cell wall thickness (larger cell sizes), 25 which confirms our results.…”
Section: Impact Strengthsupporting
confidence: 92%
“…23 In our previous work, we reported that increasing the chemical blowing agent (CBA) content led not only to lower tensile and flexural moduli, but also to lower tensile strength and elongation at break, which can be associated with lower density and larger cell size. 25 With the ever-increasing consumption of polyethylene products in recent decades, a large number of solid wastes are generated causing serious environmental issues worldwide since they do not easily degrade and remain in the environment for a long time. 26,27 Hence, seeking new ways to reuse recycled polyethylene is essential to minimize the amount of waste.…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that the impact strength decreased in all compounds with increasing GTR content due to poor adhesion at the interface between GTR and LDPE and low pressure inside the mold leading to the creation of voids inside the parts. Furthermore, it can be observed that the impact strength of LDPE/NRR samples is higher than that of LDPE/RR ones due to the cross-linked structure of the GTR making the particles more deformable to absorb more energy before crack initiation [21]. Therefore, the regeneration process led to lower impact strength due to a lower cross-link density inside RR particles.…”
Section: Impact Strengthmentioning
confidence: 99%
“…Increased cost related to the grinding process is observed for most of these materials. In addition, only a few polymers can be used for rotational molding since the materials require special properties such as low viscosity and high thermal stability [21]. This is the main reason why polyethylene (PE) in its several forms is used to produce rotomolded parts.…”
Section: Introductionmentioning
confidence: 99%